The Effect of the Alcoholic Extract of the Leaves of the Capparis Spinosa Plant in the Prevention of Liver and Kidney Cancer Induced by Benzo[a]Pyrene in Female Balb/c Mice - دعبول, فاطمة; نهلة نصر ابراهيم; رنا محسن عيسى (Latakia University Journal -Biological Sciences Series, 2024)
Cancer is a global health problem, its incidence increased in the early twentieth century as a result of environmental pollution resulting from the great industrial revolution that the world witnessed in addition to the lack of therapeutic or preventive measures for this disease and its high cost if any. Our current study aimed to investigate the protective effect of an extract of Capparis spinosa leaves against cancer The liver and kidneys caused by a compound of benzo[a]pyrene in vivo, the study included 60 individuals of female Balb/c mice distributed equally into four groups: the first group as a control was given water and food throughout the experiment period, the second group was dosed daily 100 mg / kg of Capparis spinosa leaf extract with oral feeding The third diseased group was injected with 30 mg/kg of benzo[a]pyrene into the abdominal peritoneum three times a week. The fourth, preventive group, was injected with 30 mg/kg of benzo[a]pyrene in conjunction with a daily dose of 100 mg/kg of Capparis spinosa leaf extract. At the end of the 10 month experiment all rats were sacrificed. The previous groups were dissected to prepare the tissue sections. A microscopic study of the liver and kidney tissues was conducted to study the carcinogenic effects and histopathological changes resulting from the administration of benzo[a]pyrene in addition to testing the role of alcoholic Capparis spinosa extract in reducing these changes. Our current results did not document the occurrence of tumors, whether benign or malignant, in the liver and kidneys of experimental mice treated with benzo[a]pyrene compound for a period of 10 months. On the other hand, the extract of alcoholic Capparis spinosa leaves played a major role in preventing the toxic effects of this compound, because it contains phenolic compounds that played an effective role as antioxidants capable of removing free radicals and getting rid of their harmful effects inside the body.